A journalistic poetics: sentimental landscapes of the present in Leila Guerriero’s "Teoría de la gravedad" (Anclajes, 2021)
The volume Teoría de la gravedad (2019) is a collection of columns by Leila Guerriero published in the Spanish newspaperEl País between 2014 and 2019. Their thematic content (loss, love, fear, death, writing) and narrative strategy (first person and intimate), situates them in thesubjective turn and affective turnmovements. Rather than a collection of "intimate chronicles", they present journalistic poetics that seek to abandon the usual confines of tragedy or the marginal and probe other areas of existence to deconstruct affective domains and emotional interdictions of the present. Two topics areanalyzed: one dominated by the recollection of life experience and the fiction of a referential self, and the other, made up of microfictions entitled "Instructions" and sentimental reflections in which that referential illusion, typical of the writings of the self,disappears.
Keywords: Argentina; XXI century; chronicle; Leila Guerriero; Teoría de la gravedad